Budgeting / Profit Planning and Control: Fifth Edition - Gordon Paul A; Hilton Ronald W; Welsch Glenn A (Prentice Hall International, 1988)
Schedules, Preface, General and Conceptual Issues, The Management Process, The Fundamental of Profit Planning and Control, The Profit Planning and Control Process, Application of Comprehensive Profit Planning and Control, Application of Profit Planning and Control, Planning and Controlling Revenues: Sales and Service, Planning and Controlling Production: Work-in-Process and Finished Goods Inventories, Planning and Controlling Purchases and Materials Usage: Manufacturing and Nonmanufacturing, Planning and Controlling Direct Labor Costs, Flexible Expense Budgets: Concepts and Development and Application, Planning and Controlling Capital Expenditures, Planning and Controlling Cash Flows, Completion and Application of the Profit Plan, Concepts Usually Integrated with Profit Planning and Control, Cost-Volume-Profit and Contribution Analysis, Performance Evaluation and Management Development, Analysis of Budget Variances, Perspectives and Overview, Appendix, Index.
Schedules, Preface, General and Conceptual Issues, The Management Process, The Fundamental of Profit Planning and Control, The Profit Planning and Control Process, Application of Comprehensive Profit Planning and Control, Application of Profit Planning and Control, Planning and Controlling Revenues: Sales and Service, Planning and Controlling Production: Work-in-Process and Finished Goods Inventories, Planning and Controlling Purchases and Materials Usage: Manufacturing and Nonmanufacturing, Planning and Controlling Direct Labor Costs, Flexible Expense Budgets: Concepts and Development and Application, Planning and Controlling Capital Expenditures, Planning and Controlling Cash Flows, Completion and Application of the Profit Plan, Concepts Usually Integrated with Profit Planning and Control, Cost-Volume-Profit and Contribution Analysis, Performance Evaluation and Management Development, Analysis of Budget Variances, Perspectives and Overview, Appendix, Index.